Thermal performance of thermoplastic polyurethane composites with microencapsulated piperazine pyrophosphate - Hu, Shuang; Peng, Jianwen; Tian, Jianjun; Xiao, Chong (Frontiers in Materials, 2023)
This study synthesized and investigated the efficacy of a novel flame retardant, melamine formaldehyde microencapsulated piperazine pyrophosphate (MFPAPP), in improving the thermal and flame-retardant properties of thermoplastic polyurethane (TPU). When TPU was incorporated with 30wt% MFPAPP, the limiting oxygen index (LOI) value of the TPU/MFPAPP composite increased to 38.8%, achieving a V-0 rating. The thermogravimetric test (TG) results confirmed that MFPAPP significantly enhanced the thermal stability of the TPU/MFPAPP composite, as indicated by the increased char residue at 800°C, which was up to 22.4wt%. Compared with the pure TPU samples, the peak heat release rate (PHRR) and total heat release (THR) of TPU/MFPAPP30 decreased by 53% and 45%, respectively. TPU/MFPAPP10 maintained a V-0 rating after the water immersion test, whereas TPU/PAPP degraded to a V-2 rating. Scanning electron microscopy (SEM), Raman spectra, and X-ray photoelectron spectroscopy analyses revealed that MFPAPP promoted the formation of heat-resistant and dense expanded carbon layers. In summary, MFPAPP demonstrated remarkable flame retardancy and thermal stability, making it an ideal candidate for enhancing the fire safety of TPU materials.